1985
DOI: 10.1002/bjs.1800720126
|View full text |Cite
|
Sign up to set email alerts
|

Pain and mobility after inguinal herniorrhaphy: Ineffectiveness of subcutaneous bupivacaine

Abstract: We studied pain and mobility in 101 men undergoing elective unilateral inguinal herniorrhaphy. Subcutaneous infusion of 0.5 per cent bupivacaine via a fine catheter was used as an adjunct to conventional analgesia in half of the patients. This had no effect on the perception of pain measured at 8 and 24 h by visual linear analogue, nor on the analgesics requested by the patients. The walking ability of all patients was significantly impaired 24 h postoperatively, but again bupivacaine conferred no benefit. Org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(21 citation statements)
references
References 4 publications
0
21
0
Order By: Relevance
“…The efficacy of analgesia by postoperative infusion of the wound with local anesthetic has been shown to be dependent on the anatomical plane of anesthetic administration [6, 7, 8]. Yndgaard et al [6]conducted a prospective randomized double-blind trial to compare the efficacy of subfascial and subcutaneous lidocaine for analgesia after inguinal herniotomy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The efficacy of analgesia by postoperative infusion of the wound with local anesthetic has been shown to be dependent on the anatomical plane of anesthetic administration [6, 7, 8]. Yndgaard et al [6]conducted a prospective randomized double-blind trial to compare the efficacy of subfascial and subcutaneous lidocaine for analgesia after inguinal herniotomy.…”
Section: Discussionmentioning
confidence: 99%
“…Subfascial infusion of local anesthetic was found to be significantly more effective than the subcutaneous route. Cameron and Cross [7]and Zieren et al [8]performed prospective randomized controlled studies to evaluate the efficacy of subcutaneous local anesthetic for analgesia after inguinal hernia repairs. Both studies demonstrated that subcutaneous administration of local anesthetics conferred no benefit in pain control compared with oral analgesics alone.…”
Section: Discussionmentioning
confidence: 99%
“…4,11 However, the method is limited by the short duration of analgesia after infiltration of long-acting local anesthetic bupivacaine. 26 To prolong the duration of action, epinephrine was added to local anesthetics clinically. 27 To date, the administration of adjuvant epinephrine combined with proxymetacaine or oxybuprocaine for infiltration anesthesia has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…However; the technique is limited due to the short duration of analgesia or anesthesia (Cameron and Cross, 1985). For this reason, bupivacaine is chosen for infiltration because of its longer duration of effective analgesia (Hannibal et al, 1996).…”
Section: Introductionmentioning
confidence: 99%